2018
DOI: 10.1111/ijtd.12127
|View full text |Cite
|
Sign up to set email alerts
|

Impact of employee development on job satisfaction and organizational commitment: person–organization fit as moderator

Abstract: Researchers have begun to focus on emerging markets, particularly those in Asia, because of the phenomenal growth in the size of their business sectors and a remarkable increase in their share of global business. Businesses in the developing world are now grappling with people management issues that formerly were the preserve of businesses in the West. This study aims at exploring the role of employee development in job satisfaction and organizational commitment and in particular its moderation by person–organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0
17

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 123 publications
5
90
0
17
Order By: Relevance
“…Just like what the literature mentioned, the organizational climate is the reflection of the culture and evolution of the organization [20]. On the other hand, job satisfaction has a positive impact on organizational commitment [6]. A study also demonstrated that employee resilience mediates the relationship between a learning-oriented organizational climate and proactive work behaviors [21].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Just like what the literature mentioned, the organizational climate is the reflection of the culture and evolution of the organization [20]. On the other hand, job satisfaction has a positive impact on organizational commitment [6]. A study also demonstrated that employee resilience mediates the relationship between a learning-oriented organizational climate and proactive work behaviors [21].…”
Section: Introductionmentioning
confidence: 93%
“…It is important to consider these minor details so that the organization satisfies its employees in academics. Parallel to this idea, a paper reported a positive impact on employee development initiatives on employee satisfaction [6]. Also, another study revealed that performance appraisal satisfaction associates with creative behavior and career development [7].…”
Section: Introductionmentioning
confidence: 95%
“…As far as employee training and development is concerned, a positive correlation between employee development initiative and organizational commitment has been observed [10]. It was found that employee's training affects positively organizational commitment and it ultimately reduces turnover and turnover intentions [11].…”
Section: Training and Developmentmentioning
confidence: 99%
“…This taxonomy is well-known, and commonly used in textbooks, research, and practice to categorize employee development experiences into four components: employee assessment, on-the-job experience, professional relationships, and formal courses or programs. The taxonomy allows us to capture and meaningfully classify a wide-range of contemporary learning and development activities as they occur in organizations (Hurtz & Williams, 2009;Jehanzeb & Mohanty, 2018;Noe, 2017;Noe et al, 2014) while explaining how the three recommendations emerge in development practice today. Finally, we propose a series of questions to guide future employee development research.…”
Section: Introductionmentioning
confidence: 99%